Eastern Partnership Association Agreements in the Mirror of Global Ungovernance: Where Does the DCFTA Lead? - Кормич, Анатолій Іванович; Кормич, А. І.; Кормич, Анатолий Иванович; Kormych, Anatolii I.; Завальнюк, Володимир Васильович; Завальнюк, В. В.; Завальнюк, Владимир Васильевич; Zavalniuk, Volodymyr V. (National University “Odessa Law Academy”, 2020)
The paper focuses on powers’ dissolving effects brought by Eastern Partnership Association agreements, signed with Ukraine, Moldova, and Georgia, to associated states’ governance systems and practices and the development of associations’ institutions and procedures. To that end, the research utilizes the concepts of “ungovernance” and “global ungovernance” that, in the authors’ view, possess significant explanation potential in the field. The paper reviews the emergence of said concepts, which may be traced back to the mid of 1990th. It emphasizes the main features of those concepts concerning both national states and transnational institution-building projects. The dispersion of powers due to the implementation of association agreements is caused by the extension of obligations far beyond those needed to implement the DCFTA and binding the market access with progress in other fields. Such agreement’s design brings the notions of “uncertainty” and “inconsistencies” into assessing the institutional and procedural issues of its implementation. The paper also analyses the side-effects of the lack of accession perspective, which, combined with extensive obligations towards approximation to the EU legislation, creates an “impossibility of closure” effect (i.e., impossibility to reach objectives set). Such an effect happens due to unclear goals and discouragement of actors involved in the implementation because of the absence of future membership guarantees. The paper also suggests that the implementation process’s failures may result in significant institutional and procedural rearrangements within the association agreements’ frameworks to adjust the governance mode to cope with such failures.

У статті розглядаються ефекти дифузії влади, що виникають внаслідок дії Угод про асоціацію, підписаних країнами Східного партнерства – Україною, Молдовою та Грузією, що впливають на системи та практики управління у цих державах та на розвиток інституцій та процедур у рамках асоціацій. З цією метою у статті використовуються концепції “неурядування” та “глобального неурядування”, які, на думку авторів, мають значний потенціал пояснення відповідних процесів. У статті розглядається розвиток згаданих концепцій, який розпочався з середини 1990-х років. Робиться акцент на головних особливостях цих концепцій у контексті національних держав та транснаціональних проектів інституційного будівництва. Перерозподіл повноважень внаслідок імплементації угод про асоціацію відбувається завдяки розширеним політичним зобов’язанням асоційованих країн, що значно перевищують необхідні для імплементації ГВЗВТ та прив’язки доступу до ринку та прогресу у інших сферах. Специфічний дизайн угод про асоціацію обумовлює те, що категорії “невизначеність” та “невідповідність” стають визначальними у інституційних та процедурних питаннях їх реалізації. Значна частина статті присвячена аналізу побічних ефектів поєднання відсутності норм щодо перспективи членства в ЄС із значним обсягом зобов’язань щодо наближення до законодавства ЄС, що створює ефект неможливості завершення (тобто неможливості досягнення поставлених цілей). Це відбувається через брак чітких цілей та брак мотивації акторів через відсутність гарантій майбутнього членства в ЄС. Вважається, що невдачі у процесі імплементації угод про асоціацію можуть призвести до значних інституційних та процедурних перебудов для коригування режиму управління з метою подолання таких невдач.

В статье рассматриваются эффекты диффузии власти, возникающие вследствие действия соглашений об ассоциации, подписанных странами Восточного партнерства – Украиной, Молдовой и Грузией, влияющие на системы и практики управления в этих государствах и на развитие институтов и процедур в рамках ассоциаций. С этой целью в статье используются концепции “неуправления” и “глобального неуправления”, которые, по мнению авторов, имеют значительный потенциал объяснения соответствующих процессов. В статье рассматривается развитие упомянутых концепций, которое началось с середины 1990-х годов. Делается акцент на главных особенностях этих концепций в контексте национальных государств и транснациональных проектов институционального строительства. Перераспределение полномочий в результате имплементации соглашений об ассоциации происходит благодаря расширенным политическим обязательствам ассоциированных стран, значительно превышающих необходимые для выполнения ГВЗСТ и привязки доступа к рынку и прогрессу в других сферах. Специфический дизайн соглашений об ассоциации обусловливает то, что категории “неопределенность” и “несоответствие” становятся определяющими в институциональных и процедурных вопросах их реализации. Значительная часть статьи посвящена анализу побочных эффектов сочетания отсутствия норм о перспективах членства в ЕС со значительным объемом обязательств по сближению с законодательством ЕС, что создает эффект невозможности завершения (т.е. невозможности достижения поставленных целей). Это происходит из-за нехватки четких целей и недостаточной мотивации актеров при отсутствии гарантий будущего членства в ЕС. Считается, что неудачи в процессе имплементации соглашений об ассоциации могут привести к значительным институциональным и процедурным перестройкам для корректировки режима управления с целью преодоления таких неудач.
Kormych A. Eastern Partnership Association Agreements in the Mirror of Global Ungovernance: Where Does the DCFTA Lead? / A. Kormych, V. Zavalniuk // Lex Portus. - Vol. 6. - Issue 26. - National University “Odessa Law Academy”, 2020. - P. 35-58.
Keywords: global ungovernance; governance; institutions; association agreement; DCFTA; integration; Europeanisation; Eastern partnership; глобальне неурядування; урядування; інституції; угода про асоціацію; ГВЗВТ; інтеграція; європеїзація; східне партнерство; глобальное неуправление; управление; институции; соглашение об ассоциации; ГВЗСТ; интеграция; европеизация; восточное партнерство; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science; Research Subject Categories::LAW/JURISPRUDENCE